INOVASI PERANCANGAN DAN PENGEMBANGAN MESIN AUTO RSB CASE INSERT PADA LINE G2RN#5 - Wijaya, Dwitri (LENVARI, 2025)
In response to the increasing demand for high-speed and consistent manufacturing processes in the Industry 4.0 era, PT Omron Manufacturing of Indonesia developed an automated solution known as the Auto RSB Case Insert. This system was implemented on the G2R relay production line to replace conventional manual and semi-automated methods. It integrates pneumatic actuation, pick-and-place mechanisms, and camera-based inspection to achieve precise and efficient case insertion. The design aims to reduce cycle time, minimize human error, and ensure product quality consistency. Performance evaluation confirmed that the system meets its target of a ≤3-second cycle time per unit with over 90% accuracy. This development demonstrates the effectiveness of integrated automation in improving production throughput and reliability in modern manufacturing environments.